A modified engineering critical assessment method for deeply-embedded cracks in metallic pipelines subjected to large plastic strain. (1st March 2019) - Jia, Pengyu; Jing, Hongyang; Xu, Lianyong; Han, Yongdian; zhao, Lei
Highlights: It is verified that DNV-RP-F108 is over-conservative to treat deeply-embedded cracks. To reduce the conservatism, a factor F is introduced. The factors which affect F are investigated. A conservative equation of the factor F is proposed. Abstract: The results of three-dimensional finite element analyses indicate that the normalized J -integral values of surface cracks are almost 3 times higher than those of deeply-embedded cracks, provided the sizes of the surface and deeply-embedded cracks are the same. In this paper, we introduce a factor F, which serves as an adjustment factor to reduce the degree of conservatism. The results show that F is the function of the non-dimensional deeply-embedded crack height (2 ae /t ), since F is markedly affected by 2 ae /t . Furthermore, after introducing the factor F, the crack tip constraint of the deeply-embedded cracks is found to be lower than that of the surface cracks, which gives a further conservatism in using the factor F for assessment of embedded cracks.